Revisiting Ag–π interactions with bis((pyrrol-2-yl)methylene)hydrazine: CC versus CN bond complexation. Issue 12 (7th March 2019) - Baudron, Stéphane A.; Chevreau, Hubert
Abstract : Crystallographic and theoretical investigations of the assembly of bis((pyrrol-2-yl)methylene)hydrazine with Ag(i ) salts suggest that, in the solid state, Ag–π interactions involve CC rather than CN pyrrolic bonds, in contrast with an earlier and unique report with this ligand. Abstract : Reinvestigation of the assembly of bis((pyrrol-2-yl)methylene)hydrazine with Ag(i ) salts suggests that, in the solid state, Ag–π interactions involve CC rather than CN pyrrolic bonds, in contrast with an earlier and unique report with this ligand.